PENGARUH SPORT EDUCATION MODEL DALAM PEMBELAJARAN BOLA VOLI TERHADAP SIKAP PERCAYA DIRI SISWA SEKOLAH MENENGAH PERTAMA - Tazra Fiddinnia Robin; Fahrudin; Ega Trisna Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine, analyze, and identify the Influence of SportEducation Mode in Volleyball Learning on the Self-Confidence of Students atSMPN 4 Klari. This study was conducted using a quantitative approach and usingan experimental method with a research design of The Randomized Pretest andPosttest Control Group Design. The population in this study was class VIII ofSMPN 4 Klari totaling 478 students. The sample used in this study was ClusterRandom Sampling, after the lottery was conducted, the sample in the study wasclass VIII I and VIII J totaling 80 students. The research instrument used a studentself-confidence attitude questionnaire instrument. The results of this study werethat the average before and after treatment experienced a significant increase,namely the mean pretest 135.10 to the mean posttest 149.18. The results of thecalculation of the Paired Sample T Test hypothesis test with the data obtainedfrom this study were a significance value (2-tailed) of 0.000 < 0.05. While theresults of the calculation of the Independent Samples T Test hypothesis test,namely the data obtained from this study are a significance value (2-tailed) of0.000 < 0.05. This means that from the two hypothesis tests there is a significantinfluence between the average value before treatment and the average value aftertreatment. It can be concluded that the Sport Education Model can have an effecton volleyball learning on the self-confidence of class VIII students of SMPN 4 Klari.